Respons Kognitif dalam Terpaan Konten pada Pengaruhnya terhadap Keputusan Pembelian : (Studi Eksplanatif pada Pengikut Akun Instagram @madformakeup.co) - Zahrah Nur Aulia Dewi; Kismiyati El Karimah; Teddy K. Wirakusumah (STIKes Ibnu Sina Ajibarang, 2024)
Madformakeup, a local cosmetic brand, collaborated with the movie Mean Girls in September 2023, launched a campaign through the hashtag #MakeFetchHappen on Instagram. This study aims to assess the impact of the frequency, attention, and duration of exposure to this campaign's Instagram content on purchasing decisions, mediated by the cognitive responses of followers of @madformakeup.co. Utilizing quantitative methods and path analysis, the study surveyed 79 respondents who commented on a giveaway post related to the collaboration on October 1, 2023. Data were collected through questionnaires and literature reviews. Findings reveal that the frequency, attention, and duration of exposure to the campaign content significantly affect purchasing decisions. Among these factors, the product/message thoughts cognitive response of followers—how they process and think about the product and message—shows the strongest influence on their purchasing choices.